2006
DOI: 10.1124/mol.106.024042
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Constants for (R)-[(S)-1-(4-Bromo-phenyl)-ethylamino]-(2,3-dioxo-1,2,3,4-tetrahydroquinoxalin-5-yl)-methyl]-phosphonic Acid (NVP-AAM077) Acting at Recombinant NR1/NR2A and NR1/NR2B N-Methyl-d-aspartate Receptors: Implications for Studies of Synaptic Transmission

Abstract: We have quantified the effects of the N-methyl-D-aspartate (NMDA) receptor antagonist (R)-[(S)-1-(4-bromo-phenyl)-ethylamino]-(2,3-dioxo-1,2,3,4-tetrahydroquinoxalin-5-yl)-methyl]-phosphonic acid (NVP-AAM077) at rat recombinant Nmethyl-D-aspartate receptor (NR)1/NR2A and NR1/NR2B NMDA receptors expressed in Xenopus laevis oocytes. We observed no difference in the steady-state levels of inhibition produced by NVP-AAM077 when it was either preapplied or coapplied with glutamate. The IC 50 values for NVP-AAM077 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 38 publications
5
106
0
Order By: Relevance
“…The 15-fold preference of ST3 for inhibition of GluN1/2A over GluN1/2B receptors is improved compared with described GluN2A-preferring competitive antagonists (15,(41)(42)(43). However, our kinetic modeling and fast-application patch-clamp recordings suggest that 15-fold subunit preference is not sufficient to fully distinguish between GluN1/2A and GluN1/2B receptors under conditions relevant to synaptic transmission (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The 15-fold preference of ST3 for inhibition of GluN1/2A over GluN1/2B receptors is improved compared with described GluN2A-preferring competitive antagonists (15,(41)(42)(43). However, our kinetic modeling and fast-application patch-clamp recordings suggest that 15-fold subunit preference is not sufficient to fully distinguish between GluN1/2A and GluN1/2B receptors under conditions relevant to synaptic transmission (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…That is, the antagonist will bind a subset of NMDA receptors, depending on antagonist concentration and binding affinity, and prevent agonist binding and subsequent gating of these receptors after synaptic release of glutamate; the mean lifetimes of antagonist-receptor complexes are typically much longer than the few milliseconds that glutamate is available for binding (28,29). Frizelle et al (15) used kinetic modeling to predict that, under nonequilibrium conditions relevant to those encountered during rapid release and removal of synaptic glutamate, NVP is incapable of fully inhibiting Glutamate concentration-response data in the absence or presence of antagonist were analyzed by simultaneously fitting all data to both the Schild and Hill equations using global nonlinear regression (SI Materials and Methods). This analysis yields values for glutamate EC 50 (in the absence of antagonist) and antagonist binding affinity (K i ) that best describe all of the experimental data.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we checked the contribution of synaptic and extrasynaptic NMDARs to neuronal damage after OGD in organotypic cortical cultures. The NR2A antagonists NVP-AAM077 (55,60) and TCN-201 (57) did not reduce cell death significantly ( Figure 6, D and E). It should be noted, however, that high concentrations of glycine in culture medium during reperfusion may reduce TCN-201 effectiveness (57).…”
Section: Resultsmentioning
confidence: 99%
“…45,55,56 Moreover, other researchers have argued that NVP-AAM077 is not sufficient to discriminate between NR2A-and NR2B-containing NMDA receptors with less than 10-fold selectivity. 57,58 In the ACC, our research group found that NVP-AAM007 shows great preference for the NR2A subunit and could be used as a selective antagonist for NR2A-containing NMDA receptors. 45,59 Although pharmacological agents that selectively block NR2C-or NR2D-containing receptors have not been discovered, (Ϯ)-cis-1-(phenanthrene-2-carbonyl) piperazine-2,3-dicarboxylic acid (PPDA) has been suggested to preferentially block NR2C-and NR2D-containing NMDA receptors.…”
Section: Pharmacology: Nr2a Vs Nr2b Receptor Antagonistmentioning
confidence: 99%